Recommendations on benchmarks for numerical air quality model applications in China – Part 2: Ozone and uncertainty analysis - L. Huang; X. Zhang; C. Emery; Q. Mu; G. Yarwood; H. Zhai; Z. Sun; S. Xue; Y. Wang; J. S. Fu; L. Li (Atmospheric Chemistry and Physics)
Ground-level ozone (O3) has emerged as a significant air pollutant in China, attracting increasing attention from both the scientific community and policymakers. Chemical transport models (CTMs) serve as crucial tools in addressing O3 pollution, with frequent applications in predicting O3 concentrations, identifying source contributions, and formulating effective control strategies. The accuracy and reliability of the simulated O3 concentrations are typically assessed through model performance evaluation (MPE). However, the wide array of CTMs available, variations in input data, model setups, and other factors result in a broad range of differences between simulated and observed O3 concentrations, highlighting the necessity of standardized benchmarks in O3 evaluation.